Radiation characteristics of two-slot array antenna on a concentric sectoral cylindrical resonator excited by a coupling slot - Wounchoum, Phairote; Phongcharoenpanich, Chuwong; Worasawate, Denchai; Krairiksh, Monai (My University, 2007)
This paper presents the radiation characteristics of two-slot array antenna on a concentric sectoral cylindrical resonator excited by a coupling slot. The magnetic fields inside the sectoral cylindrical resonator for the first few modes are presented with sectoral angle of 60 degrees. It shows that the appropriate mode for a slot array antenna on a concentric sectoral cylindrical resonator is the TM110 mode. The radiation patterns of two-slot array antenna on a concentric sectoral cylindrical resonator for single sector are illustrated. The location of the coupling slot is considered to find the appropriate radiation pattern. The results provide useful information for the design of switched-beam array antenna on the concentric sectoral cylindrical resonators.
Keywords: Concentric sectoral; Mode; Resonator; Slot antenna